A critical review of complementary and alternative medicine use by women with cyclic perimenstrual pain and discomfort: a focus upon prevalence, patterns and applications of use and users' motivations, information seeking and self‐perceived efficacy. (7th June 2016) - Fisher, Carole; Sibbritt, David; Hickman, Louise; Adams, Jon
Abstract: Introduction: Complementary and alternative medicine (CAM) is used for treating cyclic perimenstrual pain and discomfort. This critical review examines women's reported CAM use, its perceived effectiveness and information relating to women's attitudes, behaviors, motivations and patterns of CAM use in its treatment. Material and methods: An extensive search of the main medical databases EBSCO, CINAHL, Medline, AMED and SCOPUS, as well as additional hand searches, was conducted. Papers included were confined to those that had been peer‐reviewed, written in English and that contained original research into CAM use for cyclic perimenstrual pain and discomfort among adult women. Results: CAM, particularly herbal medicine, nutritional supplements and massage, is widely used for a range of cyclic perimenstrual pain and discomfort symptoms. A large number of CAM modalities are adopted, often simultaneously and with little professional oversight. Women's assessment of efficacy of different CAM modalities is positive, though the majority of users are self‐prescribing apparently without professional guidance. Although the uptake of CAM for cyclic perimenstrual pain and discomfort is widespread, few empirical data are available regarding which women are using CAM, their motivations for doing so and, importantly, the sources through which women receive information about CAM. Conclusions: This review highlights the extensive use of (often self‐prescribed) CAM in a number of countries to alleviate the widespread symptoms of cyclic perimenstrual pain and discomfort. An understanding of all health care use by women with perimenstrual pain and discomfort is vital to help ensure safe, effective and coordinated health care that can lead to optimal patient outcomes.